Hubungan Penggunaan Media Sosial Dengan Praktik Makanan Pendamping Air Susu Ibu (MP-ASI) Di Posyandu Kelurahan Karet Tengsin, Jakarta Pusat - Manalu, Waisaktini Margareth; Putri, Purwatiningsih (Jurnal Ilmiah Gizi dan Kesehatan (JIGK), 2025)
Inappropriate complementary feeding can be a factor in the incidence of undernutrition in infants. The provision of complementary foods must pay attention to the appropriate amount, time, texture, variety, method of administration, and cleanliness. Mothers who received online education were able to implement good complementary feeding practices by 82.6%. This study was conducted to analyze the relationship between social media use, complementary feeding practices and the incidence of undernutrition in Posyandu Karet Tengsin Village. The study used a cross-sectional design. Data analysis used Univariate and Bivariate with a gamma test. The results of this study showed that There was no significant correlation between the use of TikTok or Instagram social media with complementary feeding practice (p>0.05), with the direction of the correlation being unidirectional and the strength being very weak to strong. The conclusion of this study is that there is no relationship between use of Social media with complementary feeding practice.